Role of DIBER DRDO Technologies in Improving Livelihood Opportunities and Curtailing Migration in Uttarakhand: A Case Study and Impact Assessment - Gupta, Sanjay Mohan; Pandey, Vandana; Agarwal, Ankur; Ballabh, Basant; Bala, Madhu (Defence Life Science Journal, 2021)
Migration of local population of Uttarakhand (UK) border areas is presently serious issues for national security since; this State is sharing international border ( 650 km) with China/Tibet and Nepal. Among the various factors reported for migration, few notables are search for better livelihood, unemployment, difficult remote terrain and poor land connectivity, less productivity from agriculture due to abiotic and biotic stresses etc. Hence, measures to increase the livelihood opportunities in these border areas to curb the problem of migration through intervention of modern agro-animal technologies are essentially required. In this attempt, Defence Institute of Bio Energy Research (DIBER) has already developed various agro-animal mature technologies, in terms of high yielding and genuine quality seed/seedlings, protected cultivation technology, soil-less cultivation technology, angora farming, mushroom cultivation, medicinal and aromatic plants (MAPs) cultivation technology, hydro-fodder, etc that shown great promise and impact in increasing the farm income and livelihood opportunities for civil inhabitants of these marginal regions. This article highlights the DIBER outreach extension efforts for ensuring better livelihood opportunities to farmers of border area and also to curtail migration that will in turn increase strategic support to Army and paramilitary defence forces deployed in three border Distts (Uttarkashi, Chamoli and Pithoragarh) of UK.